Effect of argon ion irradiation on hardening and microstructure of ferritic-martensitic steel T91 - Voyevodin, V.N.; Tolstolutskaya, G.D.; Karpov, S.A.; Tikhonovsky, M.A.; Tolmachova, G.N.; Kalchenko, A.S.; Vasilenko, R.L.; Kopanets, I.E. (Вопросы атомной науки и техники, 2019)
Ferritic-martensitic steel T91 was irradiated with 1.4 MeV Ar⁺ ions to doses from 0.5 to 7 displacements per atom (dpa) at room temperature. Microstructure characterization was performed using transmission electron microscopy (TEM). TEM observations indicated that black dots and dislocation loops dominated the damage microstructure after ion irradiation. The nanoindentation technique was used to find out the changes in the hardness values with irradiation dose. Nanoindentation tests were performed at room temperature in continuous stiffness measurement mode before and after the irradiation. Nix-Gao model was used to extract the bulk-equivalent nanohardness of specimens. Pile-up of material around the indentation site that affects the calculated contact area was taken into account for correct interpretation of the mechanical properties of the irradiated material. It is shown that ion irradiation leads to hardening by 21% (ΔH ~ 0.7 GPa) which reaches quasi saturation at doses ≥ 1 dpa. Феритно-мартенситну сталь Т91 опромінювали при кімнатній температурі іонами Ar⁺ з енергією 1,4 МеВ в інтервалі доз 0,5…7 зсувів на атом (зна). Дослідження мікроструктури методом просвічувальної електронної мікроскопії показало утворення після іонного опромінення дефектів типу «чорних точок» і дислокаційних петель. Вимірювання твердості сталі проводили при кімнатній температурі методом наноіндентування в режимі безперервного вимірювання жорсткості до і після опромінення. Значення об'ємно-еквівалентної нанотвердості зразків розраховувалися з використанням моделі Нікса-Гао. При визначенні твердості сталі враховували ефект «навалу» матеріалу навколо місця вдавлення, який впливає на розрахункову площу контакту. Показано, що іонне опромінення призводить до збільшення нанотвердості на 21% (ΔН ~ 0,7 ГПа) і досягає квазінасичення при дозах ≥ 1 зна. Ферритно-мартенситную сталь Т91 облучали при комнатной температуре ионами Ar⁺ с энергией 1,4 МэВ в интервале доз 0,5…7 смещений на атом (сна). Исследование микроструктуры методом просвечивающей электронной микроскопии показало образование после ионного облучения дефектов типа «черных точек» и дислокационных петель. Измерения твердости стали проводили при комнатной температуре методом наноиндентирования в режиме непрерывного измерения жесткости до и после облучения. Извлечение значений объемно-эквивалентной нанотвердости образцов выполнялось с использованием модели НиксаГао. При определении твердости стали учитывали эффект «навала» материала вокруг места вдавливания, который оказывает влияние на расчетную площадь контакта. Показано, что ионное облучение приводит к увеличению нанотвердости на 21% (ΔН ~ 0,7 ГПа) и достигает квазинасыщения при дозах ≥ 1 сна.